Investigation of the compliance of Persian abstracts and graduate theses and Dissertations of engineering fields of Tabriz University with international standards ISO 214 - zahra Jahanban Esfahlan; afshin hamdipour; rasool zavaraqi (آموزش مهندسی ایران, 2020)
Abstract: Present study is conducted with the aim of studying the agreement of Persian abstracts and graduate theses of engineering courses of Tabriz University during 2005-2015 with international standards of ISO-214. The statistical population of this study is 342 titles for the ISO-214 standard, which relates to 4 faculties and 21 engineering disciplines. For the data analysis, descriptive statistics and inferential statistics (Chi test, Phi and Cramer tests) and Excel 2010 software and SPSS version 22 were used. Also, one checklist for the investigation of ISO 214 was implied. The results of this study showed that among faculties, the Faculty of Civil Engineering with an average of 81.95% is more consistent with the ISO-214 components. In the ISO 214 standard, the relevant components in the Soil and Fundamental Engineering, Surveying and Geomatics Engineering and Manufacturing Engineering have been observed respectively with a mean of 86.29%, 85.55%, and 84.75% higher than the other studied disciplines. among the 15 components of ISO -214 that were examined, components of the use of “verbs and pronouns in the third form” with a total of 100%, the “bibliographic information component in the abstract page” with an average of 98.75%, and the “existence of a keyword” with an average of 98.52% are in agreement with ISO-214 standards. The mean observance of the components of ISO 214 was 78.72%, which greatly compliance with the ISO 214 standard.